THE USE OF PHET SIMULATION ON PHYSICS CHAPTER WAVE AND VIBRATION IN 3T REGION - Budiarti, Indah Slamet; Lumbu, Albert (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2021)
Learning to use PhET as a virtual laboratory can improve students’ understanding of abstract concepts or material that is difficult to experiment in a real laboratory. The purpose of this local service activity is to conduct training for teachers and students at SMAN 1 Nimboran, Jayapura Regency. This is to find out how the implementation of the PhET Simulation learning media in the 3T region which stands for terdepan (frontier), terpencil (remote), and tertinggal (disadvantaged) in Indonesia. This service activity was attended by physics teachers and students of class XI-IPA at SMAN 1 Nimboran, Jayapura Regency. The method of this activity is carried out in the form of virtual laboratory training through PhET Simulation, face-to-face/offline at SMAN 1 Nimboran. The success of this training program for teachers and students can be seen from the enthusiasm and attainment of skills to use PhET Simulation smoothly. Students better understand the concepts of vibration and waves through simulation. The plan for the next stage of this service activity is to follow up for other subjects and 3T area.